A dynamic SIR model for the spread of novel coronavirus disease 2019 (COVID-19) in Malaysia / Nur Aziean Mohd Idris, Siti Khadijah Mohtar, Zaileha Md Ali, and Khadijah Abdul Hamid - Mohd Idris, Nur Aziean; Mohtar, Siti Khadijah; Md Ali, Zaileha; Abdul Hamid, Khadijah (Universiti Teknologi MARA, 2022)
The emergence of the first coronavirus disease 2019 (COVID-19) case in Malaysia has increased the number of infected cases. Hence, this study proposes a Susceptible-Infected-Recovery (SIR) epidemiological model of the COVID-19 epidemic to portray the outbreak's situation. The SIR model is numerically solved using the Fourth-order Runge-Kutta (RK4) method in Matlab®. The Euler method verifies that the graphical results of the SIR model are reliable and valid. In addition, this study analyses the stability of disease-free and endemic equilibriums of the SIR model by the Jacobian matrix. The results show the outbreak for phase 1 occurs in the first 100 days of the phase due to the increased infected cases in early March 2020. As for phase 2, the increases of infected cases in wave 2 make the outbreak occur throughout phase 2, with R0 being higher than phase 1. The infected population for phase 3 shows asymptotic behavior even though the infection rate increases, but the recovery rate is much higher than in phase 2. The local stability of the endemic equilibrium of all phases exists since the value of R0 is more than one. The system is locally asymptotic stable for all three phases since the obtained eigenvalues are real and negative.